(untitled) (Journal of Hama University, 2022)
This research aimed to evaluate the effect of the Reversed Twin –block appliance on the upper air way dimensions of Skeletal class III malocclusion using cone beam computed tomography (CBCT). The study sample consists of 20 children (14males and 6 females) selected from the orthodontic clinic at Damascus University. All subjects aged from (9-12 years) and had skeletal class III malocclusion resulting from upper jaw retrusion and lower jaw protrusion. All patients have no previous orthodontic treatment. All patients were treated with reversed twin-block appliance and CBCT images were taken before treatment (T0) and after end of treatment (T1). then, the Mimics 21 software was used to calculate some relevant linear parameters of the upper airway. The obtained data were analyzed using Spss20 and paired sample t-test. The airways showed a significant expansion of both the nasopharynx and oropharynx (P<0.001). In addition, both the nasopharynx(P=0.006) and the oropharynx (P=0.015) became more circular, while the lower pharynx dimensions decreased significantly and became more elliptical. The use of the revered twin block increases the dimensions of both the nasopharynx and the oropharynx, which may improve respiratory function. while there is a minor change in the dimensions of the hypopharynx-which become more elliptical- but may not be clinically important and does not have any negative effect on respiratory function.